Cost-Effectiveness of Alternative Integrated Pest Management Extension Methods: An Example from Bangladesh - Ricker-Gilbert, Jacob (2012)
This study examines the cost-effectiveness of alternative methods for diffusing integrated pest management practices in Bangladesh. Methods compared include farmer field schools, field days, and extension agent visits. Farmer field school participants were more likely to adopt integrated pest management practices than recipients of messages from field days and agent visits. However, due to lower costs per participant, field days were the most cost-effective means for stimulating adoption of simpler practices and extension agent visits were the most cost-effective for extending more complex practices.